Developing English Speaking Teaching Materials Through Peer Collaboration Model At MTS S Mutafawiq Aini - Rahmadini Panggabean, Rizka; Asnawi (PT Inovasi Pratama Internasional, 2026)
The objective of this research is to design, develop, and validate a set of English speaking teaching materials based on the peer collaboration model that are suitable for use by 9th-grade students at MTs S Mutafawiq Aini. This research employs a Research and Development (R&D) approach as proposed by Borg and Gall (2003), which is especially relevant for educational innovation. The R&D model offers a structured process that aims to produce educational products, such as teaching materials, that are developed and validated through rigorous procedures. This model includes a cycle of planning, developing, validating, testing, and revising the product to ensure its relevance, usability, and effectiveness in real teaching contexts. After analyzing the data, the researcher concluded that the existing speaking material is not appropriate for students and it was not enough to make students understand the material about descriptive text. They think it is difficult to learn about speaking descriptive text because the existing material is not in line with their major. They want to have a suitable material with their major that can motivate them to learn. The solution for that problem is developing the new appropriate speaking English material. Developing the material was using the R & D phases by Gall et. al. (2003) which is simplified into; (1) Gathering Data and Information; (2) Need Analysis; (3) Design Media; (4) Validate by expert; (5) Revision; (6) Final Product. The score of validation from the first validator was 95% and from the second validator was 93.3% and it was categorized as relevant. It means the material is appropriate to use as learning material for students